Da pequena à grande ciência no norte do Brasil: evolução da publicação nos Institutos Federais Amazônicos - CARDOSO, Suzana (Instituto Federal do Amapá, 2020)
It was investigated the scientific production of Federal Institutes from North Brazil, through Web of Science, from 2009 to 2018, to evaluate the consolidation of its scientific community. 665 articles were analyzed regarding (A) number of articles per year; (B) publishing scientific journals; (C) production per knowledge areas; (D) language of publications; (E) international collaborations; (F) citations; (G) research elite; and (H) grants and funding. We conclude that the north region is developing citation and production, moving from “little science” to “big science”, even though it is behind the south.